Desire thinking as a mediator of the relationship between novelty seeking and craving. (June 2015) - Caselli, Gabriele; Manfredi, Chiara; Ferraris, Annalisa; Vinciullo, Francesca; Spada, Marcantonio M.
Abstract: Background: The construct of craving has been shown to play a crucial role in the development and maintenance of addictive behaviors. Both novelty seeking and desire thinking have been identified, respectively, as important temperamental and cognitive predictors of craving. Aims: In the present study we aimed to explore the relative contribution of novelty seeking and desire thinking towards craving, hypothesizing a sequence of multiple mediating relationships starting from novelty seeking and moving onto imaginal prefiguration, verbal perseveration and craving in serial fashion. Method: A convenience sample of 270 individuals completed measures assessing novelty seeking, desire thinking, and craving relating to a chosen activity. Results: Findings showed that, controlling for age and gender, desire thinking components predicted craving over and above novelty seeking. The indirect effect from novelty seeking to craving, via desire thinking components, was significant thus supporting a multiple-mediational sequence. Finally, the relationship between imaginal prefiguration and craving was found to be partially mediated by verbal perseveration. Conclusions: The findings provide support for the conceptualization of desire thinking as an independent construct in predicting craving over and above novelty seeking. Highlights: We examined the relationship between desire thinking, temperament and craving. Findings support a multiple mediational sequence from novelty seeking to craving. Desire thinking mediates the relationship between novelty seeking and craving.